1990
DOI: 10.1143/jjap.29.l394
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Reaction of Mo on Cubic and Hexagonal SiC

Abstract: By applying a small amplitude modulation to the mean current in a mercury positive column and observing the microwave reflection from the column in the region of resonance, the mercury ionization rate may be determined. The results show better agreement with theory than do probe measurements, probably because, unlike probes, the microwaves do not disturb the ion current flow to the walls. Electron temperatures may be calculated from the ionization rate using the 'free-fall' theory proposed by Langmuir and To& … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…14 Penner has used electrochemical deposition to make nanowires at stepped edges on highly ordered pyrolytic graphite ͑HOPG͒ surfaces, [15][16][17][18] and Hara has used electrodeposition to make nanowires on a Si͑111͒ surface. 19 The nanowires were produced by first applying a very negative potential spike which resulted in nucleation along the step edge and then reducing the potential to allow for slow growth of the nuclei.…”
mentioning
confidence: 99%
“…14 Penner has used electrochemical deposition to make nanowires at stepped edges on highly ordered pyrolytic graphite ͑HOPG͒ surfaces, [15][16][17][18] and Hara has used electrodeposition to make nanowires on a Si͑111͒ surface. 19 The nanowires were produced by first applying a very negative potential spike which resulted in nucleation along the step edge and then reducing the potential to allow for slow growth of the nuclei.…”
mentioning
confidence: 99%
“…An atomically flat Si(111) surface with a step-terrace structure, which can be easily obtained by wet etching, 1) has been considered as one of the prospective templates for nanoscale assembly, since atomic steps are chemically much more reactive than terraces. [2][3][4] We have reported that atomic metal wires could be fabricated along step edges by the wet process. [5][6][7] To obtain well-controlled nanostructures, however, some advanced methods of template preparation with a given step structure are required.…”
Section: Introductionmentioning
confidence: 99%
“…Cu and Ni nanowires have been formed by controlling the Si potential with application of external biases (electrodeposition). 2,3) However, electrodeposited nanowires are too wide to be adopted for the nanodevices with atomically controlled nanostructures.…”
mentioning
confidence: 99%